PENATAAN RUANG LAUT BERDASARKAN INTEGRATED COASTAL MANAGEMENT - Dina Sunyowati (Mimbar Hukum, 2008)
The planning of coastal spatial arrangement must be put in the valid spatial planning system. Law Number 26 of 2007 on Spatial Planning and it is in fact related with land spatial planning, although that ocean and air spatial management will be arranged in separate law. The legal for coastal zone management is determined by using the principles of integrated coastal management by focusing on area or zone authority system. The integrated of coastal zones management regulations should be followed by the planning of coastal spatial arrangement. Therefore, certain synchronization at coastal zones governance is very important issue since by integrating and coordinating other related regulations and therefore conflict of norm can be minimized in the spatial planning coastal zone.